EVALUASI KEJADIAN STUNTING PADA BALITA YANG MEMILIKI RIWAYAT DIARE DAN ISPA DI PUSKESMAS RUMBIA - Sudrayani Usman; Wa Ode Salma; Asriati Asriati (NHM PRESS, 2021)
Stunting (low length- or height-for-age), in young children is the result of multiple circumstances and determinants, including antenatal, intra-uterine and postnatal malnutrition. Stunting in early life is associated with adverse functional consequences, including poor cognition and educational performance, low adult wages, lost productivity and, when accompanied by excessive weight gain later in childhood. This study aims to determine the risk factors for stunting in toddlers during the Covid 19 period at the Rumbia Health Center. This study is an analytic observational study using a Case Control Study design with a total sample of 82 (41 cases and 41 controls) using purposive sampling technique. This study involved toddlers aged 6-60 months in Rumbia District, Bombana Regency, which consisted of 4 Kelurahan and 1 Village. Analysis of research data was carried out using an odds ratio at a significant value of 0.05. Based on bivariate analysis of stunting in children under five, it was found that a history of infectious diarrheal disease with OR = 0.3 (95% CI: 0.1-1.0), acute respiratory tract infection with OR = 0.4 (CI 95 % :0,1-1,6). Birth weight, family income, mother's education level and infectious diarrheal diseases are factors related to the incidence of stunting in toddlers during the COVID-19 period, while the determinant factor for stunting in toddlers during the COVID-19 period is a history of suffering from diarrhea.